Preparation and characterizations of plasticized PMMA/PVC/Mg(ClO4)2 electrolytes - Tham, Do Quang; Mai, Tran Thi; Hoang, Thai; Dung, Nguyen Thi Kim; Tung, Nguyen Quang; Linh, Nguyen Thi Dieu; Huyen, Lai Thi; Thang, Dam Xuan; Cong, Do Van; Huynh, Mai Duc; Thai, Nguyen Thi (Vietnam Journal of Science and Technology, 2019)
Electrolyte films based on poly(methyl methacrylate) (PMMA), poly(vinyl chloride) (PVC) were prepared by using casting method with the addition 100 wt.% to 240 wt.% of dioctyl phthalate (DOP), propylene carbonate (PC) as plasticizers and Mg(ClO4)2 as an electrolytic salt. The Fourier infrared spectra (FTIR), tensile, electrical properties, surface morphology of electrolyte films were investigated. The FTIR spectra of plasticized PMMA/PVC blends indicated that there were secondary interactions between plasticizers and PMMA/PVC matrix. There were also molecular interactions between Mg(ClO4)2 and the blends, which indicated that Mg(ClO4)2 was well dissolved and solvated in the blends. Tensile results showed that Mg(ClO4)2 improved the elongation at break and the reduced tensile strength and Young’s modulus of the blends due to this salt can act as an internal lubricant for the blends. The SEM and EDX-mapping micrographs showed the wrinkled surface morphology of the electrolyte film, all raw materials were dispersed regularly into each others at molecular and ionic levels. For the electrolytes containing 10 wt.% of Mg(ClO4)2, the ionic conductivity increased with increasing plasticizer content and achieved in the range of 1.80 × 10-4 - 1.03 × 10-3 (S/cm). For the electrolyte containing 200 wt.% of the plasticizer, the ionic conductivity increased with increasing magnesium salt content and achieved in the range of 2.31 × 10-4 - 4.57 × 10-3 (S/cm).